Inside Cover. Issue 4 (12th April 2021) - Subramanian, Kaushikaram; Petzold, Heike; Seelbinder, Benjamin; Hersemann, Lena; Nüsslein, Ina; Kreysing, Moritz
Abstract: Biological cells are highly light scattering, largely precluding the optical access of light microscopes into living tissues. Using a scheme of mutation and high throughput optical selection, the authors present the directed evolution of mammalian cells towards increased transparency. The evolved cells replicate and reflect a physiological state, while showing strongly reduced light scattering, which motivates the authors to propose the generation of genetically enhanced, optically superior tissues (GHOSTs) to advance life microscopy. Further details can be found in the article by Kaushikaram Subramanian, Heike Petzold, Benjamin Seelbinder, LenaHersemann, Ina Nüsslein, and Moritz Kreysing. (e202000457 ). Abstract : Biological cells are highly light scattering, largely precluding the optical access of light microscopes into living tissues. Using a scheme of mutation and high throughput optical selection, the authors present the directed evolution of mammalian cells towards increased transparency. The evolved cells replicate and reflect a physiological state, while showing strongly reduced light scattering, which motivates the authors to propose the generation of genetically enhanced, optically superior tissues (GHOSTs) to advance life microscopy. Further details can be found in the article by Kaushikaram Subramanian, Heike Petzold, Benjamin Seelbinder, LenaHersemann, Ina Nüsslein, and Moritz Kreysing. (e202000457 ).